Effect of KH2PO4 on gene expression, morphological and biochemical characteristics of stevia rebaudiana Bertoni under in vitro conditions - Kahrizi, D.; Ghari, S. M.; Ghaheri, M.; Fallah, F.; Ghorbani, T.; Beheshti Ale Agha, A.; Kazemi, E.; Ansarypour, Z. (Cellular and Molecular Biology, 2017)
Stevia rebaudiana is one of the most important biologically sourced and low-calorie sweeteners Bertoni that has a lot of steviol glycosides. Tissue culture is the best for propagation of stevia and micro nutrients can affect both morphological traits and steviol glycosides production. Therefore, the effect of different concentrations of KH2PO4on stevia growth factors and gene expression had been studied by tissue culture methods, RT-PCR and HPLC. According the results, bud numbers had increased significantly in MS + 0.034 mMKH2PO4 media and the highest measured length was seen in plants grown under MS + 0.034 mM KH2PO4 treatment. Also, the highest growth rate (1.396 mm/d) was observed in MS + 0.034 mMKH2PO4.The best concentration of KH2PO4 for expression of UGT74G1 was 0.00425mMand the best one for UGT76G1 expression was 0.017mM. Interestingly, the best media for both stevioside and rebaudioside A accumulation was 0.017mM KH2PO4containing media. There was positive correlation between the best media for gene expression and the best one for steviol glycosides production.